Two Suns? The Algorithmic State: The Bones of the Argument - Cleave, Peter (Te Kaharoa, 2021)
The argument in the last part of the Two Suns? series was summed up as follows. There are several spaces or forms of space involved; territorial space, outer space, cyberspace and living space, And there is data to be found and owned in each of these spaces. That data may be processed using algorithms in each space and across all spaces.The argument has been developed as follows. In Part One, the bones, at least some of them, of the argument in the series may be seen in the title,Two Suns? The State of Amazon? Bezonomics, market control and the algorithmic state. Books by Brian Dumaine and Rob Hart, Bezonomics and The Warehouse respectively, were the jump off points for the discussion along with earlier work by me on incipient states. I asked about Amazon:Is it an entity that now has a force, a scale, an ethic and a set of borders that speaks of a state-like situation wherein people rely and trust Amazon to fulfil their needs?